p21 Genetic Modification as a Tumor-Suppressor Gene: A Future Target in Lung Cancer Therapy? - Adityo Wibowo; Silvana Saputri (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Lung cancer is one of the most common cancers and the leading cause of cancer death worldwide. Although early diagnosis/screening methods and treatment strategies have developed, lung cancer patient survival rates remain low. However, resistance to chemotherapy and radiotherapy causes tumor recurrence and worsening of the disease, thus being the lead cause of treatment failure. In the growth cycle of lung cancer cells, the highest p21WAF1/CIP1 gene expression was found in early-stage lung cancer and decreased in advanced lung cancer. In addition, the association between CDK inhibitors and patient survival showed that inactivation of the p21WAF1/CIP1 and p16INK4a genes was associated with lower overall survival and poor prognosis. In this review, we will focus on the role of genetic modification in lincRNA-p21 in lung cancer therapy and the importance of a combination therapeutic approach.